Stiffness and ultimate strength of tube-gusset plate joints with ring stiffener plate. (October 2021) - Qu, Songzhao; Sun, Qing; Yuan, Jun
Abstract: The stiffness of the stiffener plate of a tube-gusset plate joint (TGPJ) with a multi-ring stiffener plate is much larger than that in the chord wall. The load on the gusset plate will be concentrated in the area where the stiffener plate is located, and the joint will eventually fail in this area as a result of the ultimate state of the ring stiffener plate. This study investigated the stiffness and ultimate strength of a ring stiffener plate under an axial load. First, an experimental study was carried out on X-shaped TGPJs with double-ring stiffener plates. The failure mode of the joints was clarified, the variation law of the joint stiffness was revealed, and the rationality of using a 3% chord wall deformation as the criterion for determining the ultimate state of joints was verified. Then, based on the test results, finite element models (FEMs) of the X-type joint and ring stiffener plate were established, and their accuracy was verified. Numerical analysis results clarified the synergistic mechanism of the double-ring stiffener plate of an X-type joint, and the equivalence between the joint failure and the single-ring stiffener plate failure was revealed. Different nominal yield strength parameters (345 and 420 MPa), different dimensions ( D/t  = 32.3–55.9 and R / t r  = 6–33.3), and different load conditions (tension and compression) for ring stiffener plates were analysed, and the accuracy of the calculation methods for the limit state of the ring stiffener plates proposed in this paper was verified. A comparison showed that the 'four-hinged ring beam model' proposed in this paper did not consider the changes in the curvature of the ring beam between plastic hinges. Thus, the calculation results of the model were obviously conservative, and the 'deformation stiffness model' was more accurate than the calculation results of other methods mentioned in this paper.